Natural dispersion of biflavonoids from Garcinia madruno extracts: A green and sustainable processing to improve the solubility and dissolution rate (2023)
ABSTRACT: Garcinia madruno is rich in antioxidant biflavonoids that could be used to treat oxidativerelated diseases. Up to now, its commercial application is challenging due to the poor water solubility of biflavonoids. This work aimed to develop a green and sustainable process to improve the solubility and dissolution rate of G. madruno biflavonoids by the development of 100% natural nanodispersions using peel extracts of this neotropical fruit. Three hydroalcoholic extracts were elaborated with different concentrations of biflavonoids and epicarp proportions. The biflavonoid natural suspensions were obtained by evaporating the ethanol of the different extracts. As a control, suspensions stabilized with commercial surfactants were compared to each other. Two natural nanosuspensions with different concentrations of biflavonoids and one nanosuspension stabilized with commercial surfactants were obtained. All dispersions had submicrometric particle distribution. M3-S nanosuspension (stabilized by commercial stabilizer) was the smallest dispersion with an average particle size of 256.6 nm, whereas natural suspension (NS-1 and NS 2) had better performance in the short-term stability and improved the solubility and dissolution rate until 400% in comparison of M3-S and isolate morelloflavone. Our results demonstrated that it was possible to formulate a biflavonoid suspension using their own plant compounds as natural stabilizers.